Zinc finger protein 189 promotes the differentiation of lamina propria T helper 17.1 cells in dextran sulfate sodium-induced colitis - Zhihong Xia; Bo Hu; Min Yang; Wenjie He (Taylor & Francis Group, 2023)
The factors regulating the heterogeneity of interleukin-17A (IL-17A)-expressing CD4+ T cells in inflammatory bowel diseases remain unclear. In the current study, we characterised the expression and function of zinc finger protein 189 (ZFP189) in a murine colitis model. Mice were given dextran sulphate sodium to induce acute colitis. Flow cytometry was applied to recognise and enrich Th17 and Th17.1 cells based on the expression of IL-17A, interferon-γ (IFN-γ), C-X-C motif chemokine receptor 3 (CXCR3), and C-C motif chemokine receptor 4 (CCR4). The expression of ZFP189 in Th17 and Th17.1 cells was determined by Immunoblotting. Lentivirus-mediated ZFP189 knockdown was conducted to evaluate the effect of ZFP189 on the differentiation of Th17 and Th17.1 cells. The adoptive transfer was performed to analyse the pathogenicity of Th17.1 cells in vivo. We found that ZFP189 was mildly up-regulated in IL-17A-expressing CD4+ T cells in colonic lamina propria. Lamina propria Th17.1 cells expressed higher ZFP189 than Th17 cells. In vitro ZFP189 knockdown in CD4+ T cells did not impact Th17 cell differentiation but suppressed Th17.1 cell differentiation, as evidenced by lower T-box expressed in T cells (T-bet) and IFN-γ. When adoptively transferred into mice, ZFP189-deficient Th17.1 cells produced fewer IFN-γ, tumour necrosis factor-alpha (TNF-α), and granulocyte-macrophage colony-stimulating factor (GM-CSF) than ZFP189-expressing Th17.1 cells. Moreover, ZFP189-deficient Th17.1 cells induced less severe colitis than ZFP189-expressing Th17.1 cells, as evidenced by less body weight loss, a lower disease activity index, and a lower colon histological score. In summary, ZFP189 acts as a positive regulator of the differentiation and pathogenicity of lamina propria Th17.1 cells in colitis.